Pengendalian Kualitas Produk Elektroplating dengan Statistical Quality Control (SQC) dan Failure Mode and Effect Analysis (FMEA) di PT. Pilar Cakrawala (PILARCO) - Mochammad Fauzan Al-Alifi; Dewi Shofi Mulyati; Iyan Bachtiar (UNISBA Press, 2023)
Abstract. PT. Pilar Cakrawala is a manufacturing company engaged in electroplating or metal plating located in Karawang Regency, West Java. In running the business there are still problems that arise, one of which is not fulfilling the Service Level Agreement (SLA). Service Level Agreement (SLA) is an agreement that contains approval for an agreement, where the agreement has been agreed upon and must be fulfilled by each party involved with the promised time. The proposed methods are Statistical Quality Control (SQC) and Failure Mode and Effect Analysis (FMEA). The SQC tools are Histogram Charts, Pareto Charts, Control Charts, and Fishbone Diagrams. For FMEA, it is used as a recommendation for improvement referring to the Cause and Effect Diagram (Fishbone Diagram). Based on the results of data processing, the most dominant type of defect is crack defect with a total percentage of (52.2%), then pinhole defect (30%), then sintered defect (13%), and roughness defect (5%). The causes of defects in products are caused by human factors, machines, methods, and materials. The proposed improvement is to provide training to workers so that they are skilled in cutting and determine time limits for breaks in cutting so that overheating does not occur and the lowest RPN value is found in the type of roughness defect with an RPN value of 16 and the cause of the defect is less compaction of the mold. Proposed improvements, namely providing training to workers to be more skilled and also providing direction to workers before the production process. Abstrak. PT. Pilar Cakrawala merupakan perusahaan manufaktur yang bergerak di bidang elektroplating atau pelapisan logam yang berlokasi di Kabupaten Karawang, Jawa Barat. Dalam menjalankan bisnisnya masih terdapat permasalahan yang muncul, salah satunya tidak terpenuhinya Service Level Agreement (SLA). Service Level Aggrement (SLA) merupakan sebuah perjanjian yang berisi persetujuan terhadap suatu perjanjian, dimana perjanjian tersebut telah disepakati serta harus dipenuhi oleh setiap pihak yang terlibat dengan waktu yang telah dijanjikan. Metode yang diusulkan yaitu Statistical Quality Control (SQC) dan Failure Mode and Effect Analysis (FMEA). Adapun alat SQC yaitu Grafik Histogram, Diagram Pareto, Peta Kendali (Control Chart), dan Diagram Sebab Akibat (Fishbone Diagram). Untuk FMEA digunakan sebagai rekomendasi perbaikan mengacu dari Diagram Sebab Akibat (Fishbone Diagram). Berdasarkan hasil pengolahan data jenis defect yang paling dominan yaitu defect crack dengan jumlah persentase sebesar (52,2%), kemudian defect pinhole sebesar (30%), lalu defect sinter sebesar (13%), dan defect roughness sebesar (5%). Penyebab terjadinya kecacatan pada produk disebabkan oleh faktor manusia, mesin, metode, dan material. Usulan perbaikan yaitu memberikan pelatihan kepada pekerja sehingga terampil dalam melakukan pemotongan dan menentukan batasan waktu untuk istirahat dalam melakukan pemotongan agar tidak terjadi overheating dan nilai RPN terendah terdapat pada jenis defect roughness dengan nilai RPN 16 serta penyebab kecacatannya yaitu pemadatan cetakan kurang padat. Usulan perbaikan yaitu pemberian training kepada pekerja agar lebih terampil dan juga memberikan arahan kepada pekerja sebelum proses produksi.